AN ANALYTICAL STUDY OF TAMIL CULTURAL HERITAGE WITH REFERENCE TO SANGAM AGE - Dr. R. Rajeshwari (LPPM Universitas Malikussaleh - Indonesia, 2023)
Over the course of two millennia, Tamil Nadu has amassed a rich cultural history that continues to flourish today. The significant cultural heritage of Tamil Nadu developed under the rule of dynasties that ruled the state at various times throughout history. Tamil Nadu is a representation of the unique Dravidian culture that emerged under the patronage of several kingdoms over the course of history. The social, economic, religious, and cultural activities of the Tamil people throughout the Sangam Age are what make Tamil Nadu and the Sangam Age special. During this time, there was progress across the board. These changes are documented in Sangam literatures and archaeological discoveries. During the Sangam era, Tamil society was split into a number of factions. The Vedic caste system of Brahmanas, Kshatriyas, and Sudras did not exist in early Sangam Age Tamil society. This classification may be considered to generally equate to the Vedic Social division; nevertheless, the earliest of the Sangam literature, Tolkappiyam, makes reference to the four divisions common in the Sangam society, namely Anthanar, Arasar, Vaislyar, and Vellalar. Purananuru, another work from the Sangam, includes references to ancient Tamil tribes including the Thudiyan, Pannan, and Kadamban. The Sangam Age's intricate social structure can be seen in these divisions. Although Tamil Nadu is one of India's most urbanised states, the vast majority of its citizens still reside in rural areas.